Aspergillus tracheobronchitis in COVID-19 patients with acute respiratory distress syndrome: a cohort study. Issue 5 (5th May 2022) - Koehler, Philipp; von Stillfried, Saskia; Garcia Borrega, Jorge; Fuchs, Frieder; Salmanton-García, Jon; Pult, Fabian; Böll, Boris; Eichenauer, Dennis A.; Shimabukuro-Vornhagen, Alexander; Kurzai, Oliver; Boor, Peter; Kochanek, Matthias; et al.
Since the beginning of the coronavirus disease 2019 (COVID-19) pandemic, patients with acute respiratory distress syndrome (ARDS) due to SARS-CoV-2 showed a profoundly altered immune system and received immune-modulating therapeutic interventions. This enhanced the susceptibility for fungal superinfections [1, 2]. With the first reports of COVID-19-associated pulmonary aspergillosis (CAPA) the 2020 European Confederation of Medical Mycology (ECMM)/International Society for Human and Animal Mycology (ISHAM) consensus criteria were proposed [3, 4] and Aspergillus tracheobronchitis (ATB) was distinguished as a sub-entity in CAPA [4–6]. During bronchoscopy, ATB presents as ulcerations, pseudomembranes, plaques and eschars, possibly combined with tracheal stenosis [5]. Facing the risk of transmission and SARS-CoV-2 infection of examiners during bronchoscopy, blind suctioning of upper airway samples has been implemented with tracheal aspirates (TA) and non-bronchoscopic lavages. These techniques preclude inspection of the airways, so that ATB cannot be diagnosed beyond the level of suspicion. To study ATB in CAPA patients, we performed a retrospective, single-centre cohort study. Comprehensive work-up is needed for COVID-19 ARDS patients, especially when suspecting invasive fungal infections. Aspergillus tracheobronchitis has a substantial prevalence in patients with CAPA accounting for an overall mortality of 75% in this study. https://bit.ly/3uF3FZU